2006
DOI: 10.2174/156720206776875902
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ischemia and Angiogenesis

Abstract: Angiogenesis occurs in a wide range of conditions. As ischemic tissue usually depends on collateral blood flow from newly produced vessels, acceleration of angiogenesis should be of therapeutic value to ischemic disorders. Indeed, therapeutic angiogenesis reduced tissue injury in myocardial or limb ischemia. In ischemic stroke, on the other hand, angiogenic factors often increase vascular permeability and thus may deteriorate tissue damage. In order to apply safely the therapeutic angiogenesis for ischemic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 93 publications
2
56
0
1
Order By: Relevance
“…, which is generally compatible with the definitions of several other investigators secretion is induced by ischemia (37,38).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…, which is generally compatible with the definitions of several other investigators secretion is induced by ischemia (37,38).…”
Section: Introductionsupporting
confidence: 89%
“…In order to safely apply therapeutic angiogenesis for ischemic stroke treatment, elu-CD133 + cells, as an EPC-enriched population, provided a marker of cerebrovascular function (93). They demoncidating its precise mechanism is mandatory (37). Upregulation and increased phosphorylation of eNOS strated that circulating EPCs increased after the onset of improves endothelium-dependent vasodilation (35,48).…”
Section: In Myocardial Infarctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have shown that post-ischemic angiogenesis plays a crucial role in the recovery of blood flow in affected tissue (45)(46)(47). Thus, angiogenic vessels in the ischemic boundary zone may contribute to recovery of tissue at risk by restoring metabolism in surviving neurons or cardiomyocytes as well as provide the essential trophic support to newly generated neuronal or cardiac cells.…”
Section: Discussionmentioning
confidence: 99%
“…10 Stroke leads to angiogenesis in the ischemic hemisphere and peri-infarct area. 11 This area is hypoxic, which probably triggers angiogenesis through the vascular endothelial growth factor system. 12 Neuroblasts migrate in association with blood vessels in the mouse striatum during the first weeks after stroke.…”
mentioning
confidence: 99%